2021
DOI: 10.54910/sabrao2021.53.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and cytological features of onion bulbs and leaves collected from various ecogeographical origins

Abstract: Against the background of global climate change, drought stress has become one of the environmental limiting factors that can significantly influence the growth and development of crop plants. Drought stress conditions also cause changes in plant physiological and metabolic processes. The influence of soil drought on the mineral composition of the leaves of two Actinidia species with С3-type photosynthesis, namely, Actinidia argutа (Siebold & Zucc.) Planch. ex Miq. cultivar ‘Taezhny Dar’ and Actinidia kolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These three karyotypes revealed that shallot plants have symmetrical karyotypes. The symmetrical karyotype is a karyotype with a uniform chromosome type and is considered more primitive than an asymmetric karyotype (Ermayanti et al, 2019;Nemtinov et al, 2021). The ideogram results revealed that the chromosome lengths between control and Bio-Catharantin treatments were different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These three karyotypes revealed that shallot plants have symmetrical karyotypes. The symmetrical karyotype is a karyotype with a uniform chromosome type and is considered more primitive than an asymmetric karyotype (Ermayanti et al, 2019;Nemtinov et al, 2021). The ideogram results revealed that the chromosome lengths between control and Bio-Catharantin treatments were different.…”
Section: Resultsmentioning
confidence: 99%
“…Shallots are one of the most indemand commodities, as almost every typical Indonesian dish, and are used either as a condiment or as a flavoring. Another use of shallots is in traditional medicines (Nemtinov et al, 2021). It can be used to relieve fever by rubbing the oil all over the body.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen, phosphorus, and potassium concentrations ranged from 0.95%, 0.38%, and 1.93% (control treatment) to 2.94%, 0.93%, and 4.71% (1.0 g/L Nano NPK + 0.5 g/L algae extract), respectively, and the micronutrients Fe, Mn, Zn, and Cu concentrations ranged from 42.77%, 33.6%, 81.43%, and 16.40% (control treatment) to 219.10%, 76.4%, 104.23%, and 32.27% (1.0 g/L Nano NPK + 0.5 g/L algae extract), correspondingly. The smaller size, the higher the specific surface area, and the reactivity of biostimulants (nanofertilizers) may affect nutrient solubility, diffusion, and availability to plants (Singh et al, 2013;Nemtinov et al, 2021;Billa et al, 2022;Maharijaya et al, 2023). The use of nanoscale fertilizers may additionally assist in minimizing nutrient loss through leaching or run-off, restricting its speedy degradation and volatility, improving the nutrient quality and fertility of the soil, and promoting crop productivity in the long run (Rautela et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, onions play a role in inhibiting cholesterol synthesis and lowering fbrinogen levels [4]. Moreover, onion bulbs exhibit elevated levels of dry solids and soluble carbohydrates, whereas the green leaves are abundant in nitrogen compounds, minerals, and vitamins [5].…”
Section: Introductionmentioning
confidence: 99%